(untitled) - Food and Agriculture Oranization of United Nations (Rome, 2006)
Opening session, plenary presentations, opening for strategic and policy innovations at the river basin level, options for technical and managerial improvements at the system and level.
Keywords: Water conservation,Bảo tồn nguồn nước,Nước tưới tiêu,Water resources development,Irrigation water,Phát triển nguồn nước; China,Trung Quốc,Trung Quốc,China,China,Trung Quốc